Characterization of viral insulins reveals white adipose tissue-specific effects in mice - Chrudinová, Martina; Moreau, François; Noh, Hye Lim; Páníková, Terezie; Žáková, Lenka; Friedline, Randall H; Valenzuela, Francisco A; Kim, Jason K; Jiráček, Jiří; Kahn, C. Ronald; Altindis, Emrah (Molecular metabolism, 2021)
OBJECTIVE: Members of the insulin/insulin-like growth factor (IGF) superfamily are well conserved across the evolutionary tree. We recently showed that four viruses in the Iridoviridae family possess genes that encode proteins highly homologous to human insulin/IGF-1. Using chemically synthesized single-chain (sc), i.e., IGF-1-like, forms of the viral insulin/IGF-1-like peptides (VILPs), we previously showed that they can stimulate human receptors. Because these peptides possess potential cleavage sites to form double chain (dc), i.e., more insulin-like, VILPs, in this study, we have characterized dc forms of VILPs for Grouper iridovirus (GIV), Singapore grouper iridovirus (SGIV) and Lymphocystis disease virus-1 (LCDV-1) for the first time. METHODS: The dcVILPs were chemically synthesized. Using murine fibroblast cell lines overexpressing insulin receptor (IR-A or IR-B) or IGF1R, we first determined the binding affinity of dcVILPs to the receptors and characterized post-receptor signaling. Further, we used C57BL/6J mice to study the effect of dcVILPs on lowering blood glucose. We designed a 3-h dcVILP in vivo infusion experiment to determine the glucose uptake in different tissues. RESULTS: GIV and SGIV dcVILPs bind to both isoforms of human insulin receptor (IR-A and IR-B) and to the IGF1R, and for the latter, show higher affinity than human insulin. These dcVILPs stimulate IR and IGF1R phosphorylation and post-receptor signaling in vitro and in vivo. Both GIV and SGIV dcVILPs stimulate glucose uptake in mice. In vivo infusion experiments revealed that while insulin (0.015 nmol/kg/min) and GIV dcVILP (0.75 nmol/kg/min) stimulated a comparable glucose uptake in heart and skeletal muscle and brown adipose tissue, GIV dcVILP stimulated 2-fold higher glucose uptake in white adipose tissue (WAT) compared to insulin. This was associated with increased Akt phosphorylation and glucose transporter type 4 (GLUT4) gene expression compared to insulin in WAT. CONCLUSIONS: Our results show that GIV and SGIV dcVILPs are active members of the insulin superfamily with unique characteristics. Elucidating the mechanism of tissue specificity for GIV dcVILP will help us to better understand insulin action, design new analogs that specifically target the tissues and provide new insights into their potential role in disease.
Keywords: inzuliny; Insulin; Receptor, Insulin; Glucose; Iridoviridae; Cell Line; inzulin; receptor IGF typ 1; fosforylace; Antigens, CD; CD antigeny; Iridovirus; Insulin-Like Growth Factor I; signální transdukce; Phosphorylation; glukosa; Signal Transduction; bílá tuková tkáň; Adipose Tissue, White; hnědá tuková tkáň; receptor inzulinu; insulinu podobný růstový faktor I; Animals; lidé; Receptor, IGF Type 1; Insulins; Humans; zvířata; myši inbrední C57BL; myši; buněčné linie; Mice, Inbred C57BL; Mice; Adipose Tissue, Brown; iridoviry